Digital vs. physical ear-nose-and-throat specialist assessment screening for complicated hearing loss and serious ear disorders in hearing-impaired adults prior to hearing aid treatment: a randomized controlled trial - Siggaard, Lene Dahl; Jacobsen, Henrik; Hougaard, Dan Dupont; Høgsbro, Morten (Frontiers in Digital Health, 2023)
This study introduces a digital assessment tool for asynchronous and remote ear-nose-and-throat (ENT) specialist assessment screening for complicated hearing loss and serious ear disorders in hearing-impaired adults prior to hearing aid (HA) treatment. The +60 population will nearly double from 12% to 22% between 2015 and 2050 increasing the incidence of age-induced hearing impairment and the need for hearing rehabilitation. If undiagnosed, age-related hearing loss negatively affects quality of life by accelerating social distancing and early retirement as well as increasing risk of anxiety, depression, and dementia. Therefore, innovative measures are essential to provide timely diagnostics and treatment. A total of 751 hearing-impaired adults without previous HA usage or experience were randomly assigned to digital or physical ENT specialist assessment screening prior to HA treatment initiation in 20 public and private hearing rehabilitation and ENT specialist clinics in the North Denmark Region. A total of 501 test group participants were assigned to digital assessment screening and 250 control group participants to physical assessment screening prior to HA treatment. In all, 658 (88%) participants completed the trial and were eligible for analysis. Digital screening sensitivity (0.85, 95% confidence interval (CI) 0.71 to 0.94) was significantly higher than physical screening sensitivity (0.2, 95% CI 0.03 to 0.56). Screening specificity was high for both assessment methods. In a setting where hearing-impaired adults were assessed for HA treatment, digital ENT specialist assessment screening did not compromise patient safety or increase the risk of misdiagnosis in patients with complicated hearing loss and/or serious ear disorders when compared to physical ENT specialist assessment screening.